Quantitative analysis of lung elastic fibers in idiopathic pleuroparenchymal fibroelastosis (IPPFE): comparison of clinical, radiological, and pathological findings with those of idiopathic pulmonary fibrosis (IPF) - Enomoto, Noriyuki (BioMed Central, 2014)
BACKGROUND: The pathological appearance of idiopathic pleuroparenchymal fibroelastosis (IPPFE) with hematoxylin-eosin staining is similar to that of usual interstitial pneumonia (UIP) in patients with idiopathic pulmonary fibrosis (IPF). The amount of elastic fibers (EF) and detailed differences between IPPFE and IPF have not been fully elucidated. The aim of this study was to quantify the EF and identify the differences between IPPFE and IPF. METHODS: We evaluated six patients with IPPFE and 28 patients with IPF who underwent surgical lung biopsy or autopsy. The patients’ clinical history, physical findings, chest high-resolution computed tomography (HRCT) findings, and pathological features of lung specimens were retrospectively evaluated. The amounts of EF in lung specimens were quantified with Weigert’s staining using a camera with a charge-coupled device and analytic software in both groups. RESULTS: Fewer patients with IPPFE than IPF had fine crackles (50.0% vs. 96.4%, p = 0.012). Patients with IPPFE had a lower forced vital capacity (62.7 ± 10.9% vs. 88.6 ± 21.9% predicted, p = 0.009), higher consolidation scores on HRCT (1.7 ± 0.8 vs. 0.3 ± 0.5, p < 0.0001), lower body mass indices (17.9 ± 0.9 vs. 24.3 ± 2.8, p < 0.0001), and more pneumothoraces than did patients with IPF (66.7 vs. 3.6%, p = 0.002). Lung specimens from patients with IPPFE had more than twice the amount of EF than did those from patients with IPF (28.5 ± 3.3% vs. 12.1 ± 4.4%, p < 0.0001). The amount of EF in the lower lobes was significantly lower than that in the upper lobes, even in the same patient with IPPFE (23.6 ± 2.4% vs. 32.4 ± 5.5%, p = 0.048). However, the amount of EF in the lower lobes of patients with IPPFE was still higher than that of patients with IPF (23.6 ± 2.4% vs. 12.2 ± 4.4%, p < 0.0001). CONCLUSION: More than twice the amount of EF was found in patients with IPPFE than in those with IPF. Even in the lower lobes, the amount of EF was higher in patients with IPPFE than in those with IPF, although the distribution of lung EF was heterogeneous in IPPFE specimens.